DEVELOPMENT OF INTERACTIVE MULTIMEDIA IN IMPROVING THE DIGITAL LITERACY SKILLS OF CLASS 4 STUDENTS OF sdn SDN KARANG TENGAH 3 - Rochman, Fatkhur; Hunaifi, Abdul Aziz; Santi, Novi Nitya (Universitas Labuhanbatu, 2023)
The background of this research was carried out by means of classroom observations and interviews with teachers and students. Based on the results of interviews and observations obtained data that the use of teaching materials such as learning media is still lacking. Teaching materials that are often used are textbooks and blackboards. The solution to overcome the problem is to develop learning media, namely smart apps Creator. The aims of the study were: (1) to determine the validity of interactive multimedia, (2) to determine the practicality of interactive multimedia, (3) to determine the effectiveness of interactive multimedia. This research is a type of development research (R&D) using the Borg and Gall development model through 10 stages (1) research and data collection, (2) planning, (3) product draft development, (4) initial field trials, (5) revision design, (6) field trials, (7) product improvement, (8) trial use, (9) final product improvement, (10) dissemination and implementation.The Borg and Gall stage is used to analyze and find out the needs at school. This stage is to determine and design the product to be developed. The Development stage of the final product is different from other products. The disseminate stage is used for the product dissemination process through validation. The conclusion of this study: Interactive multimedia is said to be very valid with a percentage of 85%. The results of the response of the learning media teacher are said to be very practical with a percentage of 86%. Interactive Multimedia. said to be very effective because after a limited trial it got a percentage of 86% and an extensive trial got 85%.Keywords: Smartbook Learning Media; fictional stories; East Javanese folklore.Abstrak Penelitian ini dilatarbelakangi oleh dilakukan dengan cara observasi kelas dan wawancara dengan guru dan siswa. Berdasarkan hasil wawancara dan observasi yang diperoleh data bahwa penggunaan bahan ajar seperti media pembelajaran masih kurang. Bahan ajar yang sering dipakai lebih ke buku teks dan papan tulis. Adapun solusi untuk mengatasi permasalahan ialah mengembangkan media pembelajaran yaitu smart apps Creator. Tujuan dari penelitian ialah: (1) untuk mengetahui kevalidan multimedia Interaktif, (2) untuk mengetahui kepraktisan multimedia Interaktifk, (3) untuk mengetahui keefektifan multimedia Interaktif. Penelitian ini termasuk jenis penelitian pengembangan (R&D) menggunakan model pengembangan Borg and Gall melalui 10 tahapan (1) penelitian dan pengumpulan data, (2) perencanaan, (3) pengembangan draf produk, (4) uji coba lapangan awal, (5) revisi desain, (6) uji coba lapangan, (7) penyempurnaan produk, (8) uji coba pemakaian, (9) penyempurnaan produk akhir, (10) desiminasi dan implementasi.Tahap Borg and Gall digunakan menganalisis dan mencari tahu kebutuhan di sekolah. Tahap tersebut guna menentukan dan merancang produk yang dikembangkan. Tahap Development hasil final produk berbeda dengan produk lain. Tahap disseminate digunakan guna proses penyebaran produk melalui validasi. Kesimpulan penelitian ini: multimedia Interaktif dikatakan sangat valid dengan presentase sebesar 85 %. Hasil dari respon guru media pembelajaran dikatakan sangat praktis dengan presentase sebesar 86%. Multimedia Interaktif. dikatakan sangat efektif sebab setelah uji coba terbatas mendapatkan presentase sebesar 86% dan suji coba luas mendapatkan 85%.kata Kunci: Multimedia Interaktif, Literasi Digital, Media Social .